RNA-seq provides insights into potato deubiquitinase responses to drought stress in seedling stage - Tang, Xun; Sun, Fujun; Zhang, Ning; Rana, Birendra Bahadur; Kharel, Raju; Luo, Pan; Si, Huaijun (Frontiers in Plant Science, 2023)
Ubiquitination is a specific protein degradation and reversible post-translational modification process that can be reversed by deubiquitinase (DUBs). DUBs can hydrolyze and release ubiquitin in the substrate protein so that the substrate can avoid degradation or change its activity, and it has an impact on plant growth and development, cell cycle, abiotic stress response, and other biological processes. Transcript sequences of potato varieties "DM1-3", "Atlantic" and "Cooperation-88" downloaded from Potato Genome Resources were used for genome-wide identification of the DUB gene family using Hidden Markov Models and verified in the NCBI CD-Search tool. The characteristics of DUB genes from different potato varieties were analyzed including subcellular localization, gene structural motifs, phylogenetic tree, and sequence homology. Polyethylene glycol 6000 (PEG6000) induced drought stress transcriptome analysis was performed on the "Atlantic", and differentially expressed genes were screened, with emphasis on the characterization of deubiquitinase. DUB genes have a complex gene structure, often with a large number of exons and alternative splicing. Their promoters contain abundant abiotic stressresponsive elements, such as 425 MYC, 325 ABRE, and 320 MYB. There are also a large number of orthologous genes in the DUBs of the three potato varieties, and these genes are often clustered in similar regions on the genome. We performed transcriptome sequencing of the potato under PEG-induced drought stress and analyzed it for the first time using the Atlantic as a reference genome. We identified a total of 6067 down-regulated differentially expressed genes (DEGs) and 4950 up-regulated DEGs under PEG-induced drought stress. We screened the expression of DUBs and observed that 120 DUBs were upregulated where most of them functioned in the nucleus, and the interacting proteins of DUBs were also localized in the nucleus. We have comprehensively identified and analyzed potato DUBs, and the accurately aligned transcriptome data which will further deepen the understanding of DUBs involved in the regulation of osmotic stress.